2001
DOI: 10.1128/jvi.75.17.8016-8020.2001
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-Directed Targeting of Retroviral Vectors via Cell Surface Antigens

Abstract: Targeted stable transduction of specific cells is a highly desirable goal for gene therapy applications. We report an efficient and broadly applicable approach for targeting retroviral vectors to specific cells. We find that the envelope of the alphavirus Sindbis virus can pseudotype human immunodeficiency virus type 1-and murine leukemia virus-based retroviral vectors. When modified to contain the Fc-binding domain of protein A, this envelope gives a significant enhancement in specificity in combination with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
124
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(127 citation statements)
references
References 26 publications
2
124
0
Order By: Relevance
“…Lentiviruses pseudotyped with the modified Sindbis virus envelope protein have been shown to bind and enter cells when an appropriate monoclonal antibody is attached. 17,18,31,33 We used this approach to show that lentiviruses engineered to express this Fc-binding domain of protein A and then incubated with antibodies to EGFR or HER-2 could readily infect C4-2 ( Figure 5) and LNCaP cells (data not shown). As EGFR is more ubiquitous and often associated with normal epithelia cells, HER-2 is the preferred target antigen for malignant cells.…”
Section: Her-2 Targeting Of Prostate Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Lentiviruses pseudotyped with the modified Sindbis virus envelope protein have been shown to bind and enter cells when an appropriate monoclonal antibody is attached. 17,18,31,33 We used this approach to show that lentiviruses engineered to express this Fc-binding domain of protein A and then incubated with antibodies to EGFR or HER-2 could readily infect C4-2 ( Figure 5) and LNCaP cells (data not shown). As EGFR is more ubiquitous and often associated with normal epithelia cells, HER-2 is the preferred target antigen for malignant cells.…”
Section: Her-2 Targeting Of Prostate Cancermentioning
confidence: 99%
“…26 Dubuisson and Rice 30 showed that the receptor-binding properties of Sindbis virus could be disrupted by insertion of short peptides (11 aa) into defined regions of the E2 glycoprotein but with retention of all other replication functions. An IgGbinding domain (ZZ domain) of Staphylococcus aureus protein A has been inserted within the E2 glycoprotein 31 and lentivirus or Sindbis vectors have been constructed with this modified envelope. By incubating with any IgG antibody, the ZZ domain and the Fc region of IgG form a tight complex.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, screening of a large panel of pseudotyped vectors established the superiority of the gibbon ape leukemia virus (GALV) and the cat endogenous retroviral glycoproteins (RD114) for transduction of progenitor and differentiated hematopoietic cells [22,34,[42][43][44][45]. Finally, owing to the capacity of the influenza virus, Sindis virus, MLV and GALV glycoproteins, among others, to pseudotype MLV and lentiviral vectors [22,25,46], several Engineering Lentiviral Vectors S85 approaches can be undertaken to modify their tropism in order to modify the host range of vectors (see below).…”
Section: Properties Of Lenti-vectors Pseudotyped With Heterologous Glmentioning
confidence: 99%
“…Non-retroviral glycoproteins include those derived from vesiculoviruses [9,10], lyssaviruses [11,12], arenaviruses [13], hepadnaviridae [14], flaviviridae [15,16], paramyxoviridae [17,18], orthomyxoviruses [19][20][21][22], filoviruses [17,23], and alphaviruses [24][25][26]. These foreign glycoproteins can be distinguished by the cell-surface receptors they bind, their architecture and topology and their cell entry properties.…”
Section: Introductionmentioning
confidence: 99%